Analisa Kerusakan Pompa OCCWP Pada Pembangkit Listrik Tenaga Uap 2 x 115 MW - Sianturi, Tambos; Hutauruk, Sindak; Sihombing, Fiktor (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2021)
The use of pumps in the industrial world, especially in power plants, cannot be separated from problems that arise that can cause losses. The research was conducted at PLTU 2 X 115 MW by taking a case that had happened to the pump, namely the Open Cycle Cooling Water Pump 2A. The analytical method used in this final project is the vibration analysis method, namely by reading the spectrum of the data retrieval results so that it can be seen what happens to the equipment that experiences an increase in vibration. Bearing damage can be seen in the spectrum image of the measurement results, where the appearance of the spectrum in the high frequency range is an indication of bearing damage. And the high vibration which reaches 13.06 mm/s and is already in the danger category based on ISO 10816-3.